2021
DOI: 10.1186/s40537-021-00475-1
|View full text |Cite
|
Sign up to set email alerts
|

Apply machine learning techniques to detect malicious network traffic in cloud computing

Abstract: Computer networks target several kinds of attacks every hour and day; they evolved to make significant risks. They pass new attacks and trends; these attacks target every open port available on the network. Several tools are designed for this purpose, such as mapping networks and vulnerabilities scanning. Recently, machine learning (ML) is a widespread technique offered to feed the Intrusion Detection System (IDS) to detect malicious network traffic. The core of ML models’ detection efficiency relies on the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…Pandey, Sonal, Lal, and Ram and Schultz et al proposed a study to improve the accuracy and speed of Opcode-based Android malware detection using machine learning techniques [20]. In 2021, Amirah Alshammari and Abdulaziz proposed a method to efficiently detect and analyze malicious network traffic in cloud computing by applying machine learning technology [21]. In 2020, Firoz Khan et al [22] suggested that malicious URL detection is an important part of many cybersecurity applications and has provided a robust way to incorporate the necessary security measures into machine learning strategies.…”
Section: Malicious File Detection Methodsmentioning
confidence: 99%
“…Pandey, Sonal, Lal, and Ram and Schultz et al proposed a study to improve the accuracy and speed of Opcode-based Android malware detection using machine learning techniques [20]. In 2021, Amirah Alshammari and Abdulaziz proposed a method to efficiently detect and analyze malicious network traffic in cloud computing by applying machine learning technology [21]. In 2020, Firoz Khan et al [22] suggested that malicious URL detection is an important part of many cybersecurity applications and has provided a robust way to incorporate the necessary security measures into machine learning strategies.…”
Section: Malicious File Detection Methodsmentioning
confidence: 99%
“…To secure the network, real-time IDS is required with effective accuracy. Alshammari and Aldribi [130] presented a lightweight detection approach for network traffic abnormalities that includes a ML model for feeding IDS in real-time. This detection technique makes use of a dataset comprising malicious and benign data.…”
Section: Cloud Forensicsmentioning
confidence: 99%
“…Using a dataset constructed from a real cloud environment, Alshammari and Aldribi [99] built ML models to detect malicious traffic in cloud computing. The dataset used was the new ISOT CID [100], a publicly available cloud-specific dataset where the training data contained 17,296 instances and testing had 7411 instances.…”
Section: Malicious Traffic In a Cloud Environmentmentioning
confidence: 99%